Defining a Purpose (vision, mission and values) that builds greater emotional connection: Make Change Happen. - Gillingwater, Richard (ICAReAlumni Conference Proceedings, 2021)
Defining a Purpose (vision, mission and values) that builds a greater emotional connection. Feel inspired to make change happen